Polyphenol-rich foods and risk of gestational diabetes: a systematic review and meta-analysis - Pham, N.; Do, V.; Lee, Andy (Nature Publishing Group, 2018)
Animal studies have demonstrated anti-diabetic properties of several food-derived polyphenols, but data in humans remains unclear. This study aimed to review and meta-analyse evidence concerning the effect of the intake of several polyphenol-rich foods on gestational diabetes (GDM) risk. A systematic literature search was conducted in PubMed, Web of Science and Embase databases for observational studies on the association between dietary intake of foods/diets rich in polyphenols and GDM risk. Inclusion criteria were original research articles with full texts published in peer-reviewed English language journals, which investigated foods within the top 100 richest dietary sources of polyphenols and reported odds ratio/relative risk with their corresponding 95% confidence intervals. The quality of included studies was assessed using the Newcastle-Ottawa Scale. The intake of polyphenol-rich foods and dietary patterns in relation to GDM were pooled with fixed- and random-effects models. In total, 12 (10 cohort, 1 cross-sectional and 1 case-control) studies were included for the final systematic review, comprising 124,959 participants and including 5,786 women with GDM. Five studies found a significant, inverse association between the intake of polyphenol-rich foods or Mediterranean diet and GDM, whereas five studies reported no association and two exhibited a positive association. Meta-analyses further showed that the risk of GDM was about halved amongst women with the highest score of Mediterranean diet compared to those with the lowest score. The results suggest that dietary patterns rich in polyphenols may reduce the risk of GDM despite inconclusive evidence for polyphenol-rich food groups.